2023
DOI: 10.1590/1413-812320232810.09852023en
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, depression and self-efficacy among Brazilian nursing professionals during the COVID-19 pandemic

Laelson Rochelle Milanês Sousa,
Pedro Henrique Tertuliano Leoni,
Raphael Augusto Gir de Carvalho
et al.

Abstract: This aim of this study was to analyze levels of resilience, depression and self-efficacy among Brazilian nursing professionals during the COVID-19 pandemic. We conducted an analytical cross-sectional study between October and December 2020. Student’s t test, analysis of variance and multiple linear regression were used to investigate the impact of two main factors (Resilience and Self-efficacy) on depression. A total of 8,792 nursing professionals participated in the study; 5,124 (58.8%) had low levels of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this sense, self-efficacy is a fundamental variable to strengthen the link between anxiety and hardiness during the experience of stressful work situations by CCU nurses. Previous literature has shown that self-efficacy plays a mediating role between optimism and happiness, which in turn influences coping with difficult situations, since people with low self-efficacy show pessimistic attitudes in response to problematic circumstances [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, self-efficacy is a fundamental variable to strengthen the link between anxiety and hardiness during the experience of stressful work situations by CCU nurses. Previous literature has shown that self-efficacy plays a mediating role between optimism and happiness, which in turn influences coping with difficult situations, since people with low self-efficacy show pessimistic attitudes in response to problematic circumstances [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that self-efficacy plays an important role after psychological trauma, contributing to reducing short-and long-term anxiety levels through a positive evaluation of one's ability to cope with the traumatic event and its consequences [24]. During the COVID-19 pandemic, self-efficacy has been studied in nurses as a personality trait that mitigates levels of anxiety, depression and burnout generated by pandemicderived trauma [25,26].…”
Section: Introductionmentioning
confidence: 99%